2019
DOI: 10.1021/acs.iecr.9b04999
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Removal of Elemental Mercury and Arsine from a Reducing Atmosphere Using Chloride and Cerium Modified Activated Carbon

Abstract: With the goal of simultaneous removal of elemental mercury and arsine from simulated yellow phosphorus off-gas, a series of Cl–Ce modified activated carbon samples were prepared via an impregnation method and investigated. The Cl3–Ce10/AC exhibited the best performance at 150 °C, with an Hg0 removal efficiency of 92.2%, and the reaction time of AsH3 removal efficiency greater than 90% was 15.5 h. The presence of Hg0 had little impact on AsH3 removal, but conversely AsH3 significantly reduced Hg0 removal effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…In our previous experimental study, we found that HgO is formed on the catalyst surface, suggesting that lattice oxygen in the catalyst plays an important role in the heterogeneous oxidation process, crucially, the consumed lattice oxygen is replenished by gas phase oxygen [5]. Therefore, we next discuss the possible…”
Section: Mechanism Of Hg 0 Catalytic Oxidation Over the Ceo 2 (111) S...mentioning
confidence: 91%
See 4 more Smart Citations
“…In our previous experimental study, we found that HgO is formed on the catalyst surface, suggesting that lattice oxygen in the catalyst plays an important role in the heterogeneous oxidation process, crucially, the consumed lattice oxygen is replenished by gas phase oxygen [5]. Therefore, we next discuss the possible…”
Section: Mechanism Of Hg 0 Catalytic Oxidation Over the Ceo 2 (111) S...mentioning
confidence: 91%
“…Zhao et al reported the modi cation of a commercial selective catalytic oxidation (SCR) catalyst with a series of metal oxides and found that CeO 2 -modi ed SCR catalyst showed the highest Hg 0 oxidation capacity [29]. In addition, in our previous work, we found that CeO 2 can oxidize Hg 0 and AsH 3 in a reducing atmosphere [5,28]. Speci cally, the removal e ciency was better than 90% at a low reaction temperature of 150 ℃.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations